Global leadership initiatives for conflict resolution and peacebuilding - Campbell, Andrew H. 1961 (A volume in the Advances in Electronic Government, Digital Divide, and Regional Development (AEGDDRD) book series, 2018)
"This book addresses the role leaders play in the outcomes of post conflict resolution measures and peacebuilding. It explores how relationships between national leaders influence post-conflict resolution or peacebuilding and provides a reference for conflict resolution and peacebuilder scholar-practitioners and educators that challenge practitioners to examine best practices through a leadership lens"-- c Provided by publisher